Reações regioespecíficas de β-alcoxivinil trialometil cetonas com heteroaroilhidrazinas - Oliveira, Marli Redin (2004)
This work describe the regiospecific synthesis of three novel series of 1-(2-thenoyl)-, 1-(2-furoyl)- and 1-(isonicotinoyl)-3-alkyl(aryl)[heteroaryl]-5-hydroxy-5-trihalomethyl-4,5-dihydro-1H-pyrazoles, in good yields (50 91 %), from the cyclocondensation reactions of 1,1,1-trifluoro(chloro)-4-alkoxy-4-alkyl(aryl)[heteroaryl]-3-alken-2-ones, where alkyl = H and Me; aryl = Ph, 4-MePh, 4-OMePh, 4-FPh, 4-ClPh, 4-BrPh, 4-NO2Ph; heteroaryl = 2-thienyl e 2-furyl with 2-thiophenecarboxylichydrazide, furoic hydrazide and isonicotinic acid hydrazide, respectively. Subsequently dehydration reaction of 1-(2-thenoyl)-, 1-(2-furoyl)- pyrazolines trihalomethyl substituted in chloroform / P2O5, depending of the trihalomethyl substituent, furnished the corresponding 1H-pyrazoles trichloromethylated in low yields (21 29 %), or 1Hpyrazoles trifluoromethylated as mixture of regioisomers and in yields (35 36 %). The 1-isonicotinoyl pyrazolines trihalomethyl substituted was extremely resistant to dehydration reactions with chloroform / P2O5 at reflux for 48 hours or with acetic acid at reflux for 4 hours. In both cases, the 2-pyrazolines were recovery without any structural modification. All compounds have been characterized by analytical and spectral data (1H and 13C-NMR, GC-MS, and elemental analyses).